Discovery of a novel iota carrageenan sulfatase isolated from the marine bacterium Pseudoalteromonas carrageenovora - Genicot, Sabine M.; Groisillier, Agnès; Rogniaux, Hélène; Meslet-Cladière, Laurence; Barbeyron, Tristan; Helbert, William (Frontiers in Chemistry, 2014)
Carrageenans are sulfated polysaccharides extracted from the cell wall of some marine red algae. These polysaccharides are widely used as gelling, stabilizing, and viscosifying agents in the food and pharmaceutical industries. Since the rheological properties of these polysaccharides depend on their sulfate content, we screened several isolated marine bacteria for carrageenan specific sulfatase activity, in the aim of developing enzymatic bioconversion of carrageenans. As a result of the screening, an iota-carrageenan sulfatase was detected in the cell-free lysate of the marine bacterium Pseudoalteromonas carrageenovora strain PscT. It was purified through Phenyl Sepharose and Diethylaminoethyl Sepharose chromatography. The pure enzyme, Psc -CgsA, was characterized. It had a molecular weight of 115.9 kDaltons and exhibited an optimal activity/stability at pH ~8.3 and at 40°C ± 5°C. It was inactivated by phenylmethylsulfonyl fluoride but not by ethylene diamine tetraacetic acid. Psc -CgsA specifically catalyzes the hydrolysis of the 4-S sulfate of iota-carrageenan. The purified enzyme could transform iota-carrageenan into hybrid iota-/alpha- or pure alpha-carrageenan under controlled conditions. The gene encoding Psc -CgsA, a protein of 1038 amino acids, was cloned into Escherichia coli, and the sequence analysis revealed that Psc -CgsA has more than 90% sequence identity with a putative uncharacterized protein Q3IKL4 from the marine strain Pseudoalteromonas haloplanktis TAC 125, but besides this did not share any homology to characterized sulfatases. Phylogenetic studies show that P. carrageenovora sulfatase thus represents the first characterized member of a new sulfatase family, with a C-terminal domain having strong similarity with the superfamily of amidohydrolases, highlighting the still unexplored diversity of marine polysaccharide modifying enzymes.